Research Trends, Topics, and Insights on Network Security and the Internet of Things in Smart Cities - Prakoso, Velandani; Lawelai, Herman; Nurmandi, Achmad; Purnomo, Eko Priyo; Jovita, Hazel (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research investigates network security and the Internet of Things in smart cities, focusing on their vulnerability to cyber threats due to advanced technologies and widespread connectivity. The aim is to address current security challenges and develop a security vision for a sustainable smart city future. The research method involves bibliometric analysis of 517 documents from the Scopus database using the VOSviewer analysis tool and CiteSpace for network visualization analysis. The findings show increased research on network security and IoT in smart cities, focusing on operational sustainability and data security. Integrating technologies like big data, artificial intelligence, and machine learning is crucial in addressing these complex challenges. The research emphasizes the importance of network security in maintaining data integrity and confidentiality in smart cities and the integration of IoT technologies in decision-making. Recommendations include developing advanced security techniques, integrating big data and sustainability, crisis monitoring, and blockchain exploration. Further research is expected to improve network security and IoT implementation, contributing to efficiency, convenience, and quality of life in an increasingly connected urban society.